OCCURRENCE OF RABIES IN ANIMALS- A RETROSPECTIVE STUDY IN WAYANAD, KERALA, INDIA - Sachin; K. S. Prasanna; R. Anoopraj; M. Pradeep; P. Hamza; P. Vinu David; F. Ansar; A. Shruthi; A. M. Anagha; J. G. Ajith (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Rabies is zoonotic viral encephalitis targeting the nervous system of several vertebrates and transmitted mostly through the saliva of the infected host causing extensive neurological dysfunction. In this study, 873 post-mortem examinations of different species of animals were done in the Department of Veterinary Pathology, Pookode and 17.64% were diagnosed as rabies positive by using direct fluorescent test (d-FAT). Out of all the rabies positive cases, 76.6% were dogs, 9.1% large ruminants, 8.4% cats and 4.5% goats. In dogs, non-descript dogs were highest followed by Labrador, Pomeranian, German Shepherd, crossbred dogs, Rottweiler, Doberman and Spitz. The male dogs contributed about 69.5% of positive cases. Highest number of cases of rabies in animals were found during the winter season (January to March) comprising 33.76% of all the rabies cases.